Postdoctoral scholarships to promote careers in development studies: CDS experience and wider issues - Asha Amirali; James G. Copestake (University of Bath, Centre for Development Studies (CDS), 2024)
Since 2012, the Centre of Development Studies at the University of Bath has employed six post-doctoral research fellows on successive two-year contracts, funded by a private donation from an alumnus. This paper draws on this experience to reflect on how to support development studies research activities and careers. It reaffirms the case for helping promising early career researchers to build upon and move beyond their doctoral work, the value of research autonomy at this stage, and balancing research autonomy with membership of relevant specialist clusters and networks.
Keywords: 330; Development studies; postdoctoral fellowships; early career